Exploring Romanian Engineering Students' Perceptions of Covid-19 Emergency e-Learning Situation. A Mixed-Method Case Study. (2022) - Alexa, Lidia; Pîslaru, Marius; Avasilcăi, Silvia; Lucescu, Letiția; Bujor, Adriana; Avram, Elena
No abstract available